2017
DOI: 10.1038/s41467-017-01247-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic determinants of lytic polysaccharide monooxygenase reactivity on polysaccharide substrates

Abstract: Lytic polysaccharide monooxygenases (LPMOs) are industrially important copper-dependent enzymes that oxidatively cleave polysaccharides. Here we present a functional and structural characterization of two closely related AA9-family LPMOs from Lentinus similis (LsAA9A) and Collariella virescens (CvAA9A). LsAA9A and CvAA9A cleave a range of polysaccharides, including cellulose, xyloglucan, mixed-linkage glucan and glucomannan. LsAA9A additionally cleaves isolated xylan substrates. The structures of CvAA9A and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
238
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(263 citation statements)
references
References 48 publications
(77 reference statements)
18
238
0
5
Order By: Relevance
“…This finding was later confirmed upon the solution of the first LPMO‐substrate structure, wherein the Lentinus similis LPMO9A ( Ls LPMO9A) complexed with cello‐oligosaccharide ligands (cellotriose and cellohexose) confirmed that the substrates bound to the proposed surface region by both hydrophobic interactions and hydrogen bonds . Recently published crystal structures of Ls LPMO9A in complex with various types of hemicellulosic oligosaccharide ligands provided further molecular‐level evidence by which we can begin to understand the broad substrate specificity of AA9 LPMOs .…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…This finding was later confirmed upon the solution of the first LPMO‐substrate structure, wherein the Lentinus similis LPMO9A ( Ls LPMO9A) complexed with cello‐oligosaccharide ligands (cellotriose and cellohexose) confirmed that the substrates bound to the proposed surface region by both hydrophobic interactions and hydrogen bonds . Recently published crystal structures of Ls LPMO9A in complex with various types of hemicellulosic oligosaccharide ligands provided further molecular‐level evidence by which we can begin to understand the broad substrate specificity of AA9 LPMOs .…”
Section: Introductionmentioning
confidence: 69%
“…). Residues within these loop regions have previously been observed to interact with cellulosic substrates, as determined by either crystallographic or computational approaches . Compared to some of the C1‐specific LPMO structures ( Nc LPMO9F, Pc LPMO9D, and Tt LPMO9E), the L2 loop of Hi LPMO9B is extended with an insertion of 10 amino acids (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations